2015
DOI: 10.31729/jnma.2787
|View full text |Cite
|
Sign up to set email alerts
|

Length of Stay of Orthopaedic Inpatients at a Teaching Hospital in Eastern Part of Nepal

Abstract: Introduction: This study aimed to analyze the average length of stay of all inpatients in the department of Orthopaedics and to compare the variations in hospital stay between age, gender, traumatic and non-traumatic co-morbidities and modality of payment. Methods: This hospital based retrospective descriptive epidemiological study was based on patients discharged from a tertiary level health care center of eastern Nepal. Registry data of 1 year was used to calculate length of stay and analyze the variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…The median length of stay observed in this study was longer compared to literature from the developed world 26 but consistent with data from the developing world 22,24,27 . A possible explanation based on our experience could be due to little emphasis on cost effective care and resources miss match resulting in prolonged hospital stay and delay in accessing supporting services such as radiology, physiotherapy and laboratory.…”
Section: Discussionsupporting
confidence: 89%
“…The median length of stay observed in this study was longer compared to literature from the developed world 26 but consistent with data from the developing world 22,24,27 . A possible explanation based on our experience could be due to little emphasis on cost effective care and resources miss match resulting in prolonged hospital stay and delay in accessing supporting services such as radiology, physiotherapy and laboratory.…”
Section: Discussionsupporting
confidence: 89%
“…Please cite this article as: Günay The expected duration of hospitalization was 3.2 days whereas the average daily hospitalization was 16.3 patients. While the average duration of hospitalization was found to be 10.5 days in a previous study conducted in Nepal (7). In another study performed by Gholson et al (8) in USA the duration of hospital stay in total knee and hip arthroplasty surgeries was found as 3.2 days.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, patients admitted for orthopaedic attention had the longest average LoS (28 days), with some staying up to 57 days without any remarkable work-up. A study in Nepal [9] reported that an average LoS for orthopaedic inpatients at a tertiary hospital was 10.5 days. [9] A SA report on the burden and profile of spinal pathology in Cape Town recorded a median hospital stay of 19 days.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Nepal [9] reported that an average LoS for orthopaedic inpatients at a tertiary hospital was 10.5 days. [9] A SA report on the burden and profile of spinal pathology in Cape Town recorded a median hospital stay of 19 days. [10] The average LoS was 7 days in the Department of General Surgery.…”
Section: Discussionmentioning
confidence: 99%